Imobilização e estabilização de Alcalase® em Immobead 350 e em Quitosana ativada por diferentes métodos visando aplicação em reação modelo - Amorim, Kímberle Paiva dos Santos (2018)
In this work, the protease Alcalase® was immobilized initially on an epoxy-activated support ― Immobead 350. The derivative (immobilization at pH 10, for 24 hours), which showed activity of 26,1 UBANE/g, was applied in the tilapia gelatin hydrolysis, aiming to obtain peptides with antioxidant activity. After 3 reactional cycles, the insoluble biocatalyst lost the ability to produce bioactive peptides. Several immobilization conditions were then tested by altering pH medium, incubation time, loading offered, immobilized enzyme crosslinking and presence of inhibitor during the process, and also a chemical modification of the support for aldehyde groups insertion was tested. All the derivatives obtained showed lower thermal stability than the non-immobilized enzyme. Also chitosan activated with three different agents ― glutaraldehyde, divinylsulfone and glyoxyl ― was used as support for Alcalase® immobilization. Immobilization conditions such as time and pH medium were evaluated. For immobilizations in support activated with glutaraldehyde, the immobilization yield for every studied times (15h to 96h) was 100%, and the biocatalysts showed activities around 30 to 45 UBANE /g. The immobilizations in divinylsulfone-activated support showed yields of less than 60% for every studied times (24h to 96h) and values of catalytic activity around 5 to 10 UBANE/g for immobilizations at pH 7, and around 20 at 30 UBANE /g for immobilizations at pH 10. The immobilizations on chitosan activated with glyoxyl showed values of yield lower than 35% for every studied times (24h to 96h) and values of catalytic activity which did not exceed 6 UBANE/g. Thermal inactivation assays at 60 ° C and pH 8 were performed, and the most stable biocatalysts were those of immobilization on Glutaraldehyde-Chitosan at pH 7 for 72h (SF = 4,4) on DVS-Chitosan at pH 10 for 24h (SF = 3,3) and on Glyoxyl-Chitosan at pH 10 for 24h (SF = 3,3). The operational stability of the derivatives was evaluated by the hydrolysis of Azocasein. After 6 consecutive cycles, the derivatives of Glutaraldehyde-Chitosan immobilization showed no loss of activity, whereas the derivative of DVS-Chitosan immobilization at pH 10 for 24 hours retained 75,5% of its activity and the derivative of Glioxil- Chitosan immobilization at pH 10 for 24 hours retained only 10% of its activity. Thus, the Glutaraldehyde-Chitosan derivatives presented the best results of catalytic activity, thermal stability and operational stability.